2014
DOI: 10.1038/cddis.2013.552
|View full text |Cite
|
Sign up to set email alerts
|

Discrepant NOXA (PMAIP1) transcript and NOXA protein levels: a potential Achilles’ heel in mantle cell lymphoma

Abstract: Mantle cell lymphoma (MCL) is an aggressive lymphoid neoplasm with transient response to conventional chemotherapy. We here investigated the role of the Bcl-2 homology domain 3-only protein NOXA for life–death decision in MCL. Surprisingly, NOXA (PMAIP1) mRNA and NOXA protein levels were extremely discrepant in MCL cells: NOXA mRNA was found to be highly expressed whereas NOXA protein levels were low. Chronic active B-cell receptor signaling and to a minor degree cyclin D1 overexpression contributed to high NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 42 publications
3
56
0
Order By: Relevance
“…MLN4924 was reported to induce Noxa expression and intrinsic apoptosis in several cancers, but the underlying mechanism for the induction of Noxa upon MLN4924 treatment remains largely unknown (3,12,22,46). In the present study, we found that, in ESCC cells, MLN4924-induced Noxa is dependent on ATF4: first, MLN4924 blocks ATF4 turnover and induces its accumulation; second, the downregulation of ATF4 via siRNA silencing completely blocked the induction of Noxa.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…MLN4924 was reported to induce Noxa expression and intrinsic apoptosis in several cancers, but the underlying mechanism for the induction of Noxa upon MLN4924 treatment remains largely unknown (3,12,22,46). In the present study, we found that, in ESCC cells, MLN4924-induced Noxa is dependent on ATF4: first, MLN4924 blocks ATF4 turnover and induces its accumulation; second, the downregulation of ATF4 via siRNA silencing completely blocked the induction of Noxa.…”
Section: Discussionsupporting
confidence: 54%
“…BH3-only protein Noxa is a key mediator of intrinsic apoptosis (12,(46)(47)(48). MLN4924 was reported to induce Noxa expression and intrinsic apoptosis in several cancers, but the underlying mechanism for the induction of Noxa upon MLN4924 treatment remains largely unknown (3,12,22,46).…”
Section: Discussionmentioning
confidence: 99%
“…20,27,28 Encouragingly, lymphoma cells, compared to other types of cancer cells, exhibit the highest sensitivity to MLN4924. 9 Moreover, normal lymphocytes including T/B cells and peripheral blood mononuclear cells (PBMCs) are resistant to MLN4924 treatment, while lymphoma cells are shown to be very sensitive to this anticancer agent.…”
Section: Discussionmentioning
confidence: 99%
“…20 Dengler et al reported that MLN4924 killed mantle cell lymphoma (MCL) cells by stabilizing pro-apoptotic protein NOXA. 27 Interestingly, Godbersen et al found that MLN4924 thwarted microenvironment-driven NF-kB activation and induces apoptosis in chronic lymphocytic leukemia B cells. 28 These collective findings demonstrate that the neddylation pathway is required for the growth and survival of lymphoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…According to this mechanism, one would expect that FASN inhibition could be of value not only as a device for attaining antitumor effects, but also as an anticancer treatment modality. In addition, orlistat has been found to augment pro-apoptotic NOXA protein (8), thus reinforcing its possible cancer protective activity. However, preclinical studies performed on rats exposed to predisposing factors for colon cancer (i.e., receiving high fat diet alone or combined with the carcinogen compound methyl hydrazine), showed that long-term treatment with orlistat lead to severe crypt alterations of colonic mucosa, that are considered colon cancer biomarkers (9,10).…”
Section: Introductionmentioning
confidence: 93%